2014
DOI: 10.1158/1078-0432.ccr-13-1440
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Response Evaluation Using 18F-FDOPA PET in Patients with Recurrent Malignant Glioma on Bevacizumab Therapy

Abstract: Purpose This study compares the value of 3,4-dihydroxy-6-[18F]-fluoro-L-phenylalanine (18F-FDOPA) PET and MRI in assessing outcome during antiangiogenic treatment in patients with recurrent high-grade gliomas. Experimental Design Thirty patients were prospectively studied with 18F-FDOPA PET scans immediately before, and two and six weeks after start of bevacizumab therapy. 18F-FDOPA metabolic tumor volumes (MTV) as well as max and mean SUVs within this MTV were obtained. MRI treatment response was assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 34 publications
3
101
0
2
Order By: Relevance
“…Excellent results with FDOPA PET were also reported regarding the monitoring of antiangiogenic treatement [14] and for the differentiation of recurrent brain metastases from radiation-induced changes [15].…”
Section: To the Editormentioning
confidence: 96%
“…Excellent results with FDOPA PET were also reported regarding the monitoring of antiangiogenic treatement [14] and for the differentiation of recurrent brain metastases from radiation-induced changes [15].…”
Section: To the Editormentioning
confidence: 96%
“…Treatment response and outcome in bevacizumab therapy has been suggested to be better assessed by 18 F-FET and 18 F-FDOPA, compared to MRI (6,(74)(75)(76)(77). Also, reliable monitoring of TMZ and nitrosourea-based chemotherapy effects has been demonstrated in patients with recurrent HGG (9,31,64,66,70,71).…”
Section: Amino-acid Petmentioning
confidence: 99%
“…Many studies have shown that amino acid PET provides information complementary to that provided by MR imaging (23,24). Examples include better definition of the infiltration of normal brain by gliomas (25), differentiation of recurrent disease from treatment-related changes (26), assessment of the tumor response to therapy (27), and prediction of the prognosis for patients with low-grade tumors (28,29). Although PET and MR imaging studies of the brain can easily be fused retrospectively, the simultaneous acquisition of PET and MR imaging studies will further improve the coregistration of PET and MR imaging information.…”
Section: Limited Number Of Overlapping Clinical Indications For 18 F-mentioning
confidence: 99%